Severance payments and firm-specific human capital - Peter Rühmann; Jens Südekum (Georg-August-Universität Göttingen, Volkswirtschaftliches Seminar, 2001)
An increase in legally binding severance payments creates both an incentive and a disincentive for workers to invest in firmspecific human capital. Which effect prevails on balance depends on the productivity of the worker's human capital investment. For strong positive reactions, increases in severance payments can even be mutually beneficial for workers and firms.
Keywords: 330; Abfindung; Bildungsinvestition; Ökonomischer Anreiz; Bildungsertrag; Theorie